Understanding The Danger of Bullying: A Phenomenological Study on Female College Students As Victims of Cyberbullying - Kus Hanna Rahmi; Rijal Abdillah; Andreas Corsini Widya Nugraha (KRTHA BHAYANGKARA, 2024)
Cyberbullying in social media until now is a problem that has not been appropriately resolved. The presence of social media certainly has consequences in human life, including shaping cyberbullying behaviour itself. Cyberbullying is an aggressive behaviour that is carried out deliberately and repeatedly by individuals and groups using telecommunication media to harm others emotionally and psychologically so that it has an impact on the lives of individuals as victims of cyberbullying. Therefore, this study seeks to explore how to describe the dangers of bullying for students who become victims of cyberbullying. This research uses a qualitative phenomenological approach. The subjects of this study are three students who are active on social media networks and have been victims of cyberbullying. Purposive sampling techniques are used to find research subjects. Data results are analyzed using phenomenological analysis. Research shows that three of the victims have been victims of cyberbullying. Besides that, sequentially, the psychological dynamics of the third subject start with the Subject's family state, the Subject, the personality of the Subject, the Subject's daily activities, cyberbullying, the dangers of cyberbullying, and the preventive efforts of cyberbullying.